PEMANFAATAN SAMPAH ORGANIK MENJADI PUPUK KOMPOS CAIR DENGAN MENGGUNAKAN KOMPOSTER SEDERHANA (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat Universitas 17 Agustus 1945 Surabaya, 2019)
Making liquid organic fertilizer especially from household organic waste with the addition of EM4 bioactivator (Effective Microorganisms). The idea was given by the University KKN Team on 17 August 1945 to utilize organic waste and household waste in the village of Sembunganyar, Dukun District, Gresik Regency. The method of making liquid organic fertilizer is household organic waste such as vegetable scraps, fruit peels, and others separated from inorganic waste. Then the EM4 bioactivator is prepared in the sprayer. Organic waste is chopped and put in the composter, the EM4 bioactivator solution is then sprayed into the composter evenly. Within 3 weeks a liquid organic fertilizer can be produced through the process.